Influence of lipid concentration on the hydrolysis and biomethanation of lipid rich wastes - Cirne, D. G. (2004)
The influence of lipid concentration on hydrolysis and biomethanation of an artificial lipid rich (triolein) waste was evaluated. No inhibition on methane production was observed for tests with 5, 10 and 18 % (w/w, based on COD) of lipid. For higher amounts of lipid (31, 40 and 47 %) inhibition was observed. However, the process was able to recover from the inhibition. When the effect of lipase addition on enzymatic hydrolysis of lipids was studied, results showed that the higher the enzyme concentration, the more accentuated was the inhibition of the methane production. The enzyme seems to enhance the hydrolysis and produced intermediates are causing inhibition of the later steps of the degradation process. Since the VFA profiles presented similar trends for the different lipid amounts tested, the major obstacle to methane production is believed to be the LCFA formed.